THE EFFECT OF PARENTS' INCOME AND PARENTAL EDUCATION LEVEL ON STUDENTS' LEARNING INTERESTS - Eti, Novia Ayu Sapitri; Rosmiati, Neni; Berliana, Berliana (Universitas Lambung Mangkurat, 2025)
This study aims to examine the influence of parents’ income and parents’ educational level on students’ learning interest at STKIP PGRI Sukabumi. Learning interest is considered an important factor in supporting students’ academic success, and family socioeconomic background is assumed to play a significant role in shaping students’ motivation and attitudes toward learning. This research employed a quantitative research approach with a correlational design. The population of the study consisted of students at STKIP PGRI Sukabumi, from which 100 students were selected as respondents using a sampling technique appropriate to the research objectives. Three main variables were examined in this study, namely parents’ income, parents’ education level, and students’ learning interest. Data were collected using a structured questionnaire that was developed based on relevant theoretical concepts. Prior to data analysis, the research instruments were tested for validity and reliability to ensure the accuracy and consistency of the measurement. The collected data were then analyzed using simple linear regression analysis to determine the effect of parents’ income and parents’ educational level on students’ learning interest. The results of the analysis indicate that parents’ income has a significant influence on students’ learning interest. In addition, parents’ educational level also shows a significant effect on students’ interest in learning. These findings suggest that students from families with higher income and higher parental education levels tend to have stronger learning interest. Therefore, it can be concluded that parents’ socioeconomic background plays an important role in influencing students’ learning interest. The results of this study are expected to provide useful insights for educational institutions and policymakers in developing strategies to enhance students’ learning motivation.